2020
DOI: 10.1186/s13018-020-01836-x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical sagittal parameters were closely related to Neck Disability Index score after anterior cervical decompression and fusion

Abstract: Background: ACDF treatment of CSM is currently recognized as a surgical method with reliable efficacy. However, the cervical radiographic findings in a certain group of patients showed that the symptoms were not completely relieved. This study will investigate the relationship between cervical parameters and prognoses after ACDF surgery. Methods: This study collected cases of CSM treated with ACDF in Zhongda Hospital from May 2014 to June 2018. The investigators recorded gender, age, cervical sagittal paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…They analysed the interrelationships of the sagittal balance parameters of the cervical spine and showed statistically significant changes in sagittal balance parameters after surgery. The T1 slope was positively correlated with the angle of cervical lordosis (r = 0.245) and SVA (r = 0.184) [17]. The results obtained by the authors confirm the interdependence of the balance parameters, analogically to the relationships observed in the lumbar spine.…”
Section: Discussionsupporting
confidence: 71%
“…They analysed the interrelationships of the sagittal balance parameters of the cervical spine and showed statistically significant changes in sagittal balance parameters after surgery. The T1 slope was positively correlated with the angle of cervical lordosis (r = 0.245) and SVA (r = 0.184) [17]. The results obtained by the authors confirm the interdependence of the balance parameters, analogically to the relationships observed in the lumbar spine.…”
Section: Discussionsupporting
confidence: 71%
“…This study also demonstrated a moderate predictive effect of preoperative T1 slope on postoperative JOA score. Before this study, Xu ( 23 ) disclosed that T1 slope, gender, and age were all correlated with the prognosis of cervical spine surgery. Furthermore, Kontt ( 24 ) indicated a strong correlation between T1 slope and C2–C7 SVA and that the cervical sagittal is imbalanced when T1-slope was >25° or <13°.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, an increasing number of studies have compared the cervical sagittal parameters [ 2 , 3 , 4 ]. Xu Y [ 2 ] found that an increase in the T1S and NT and a decrease in the CL were risk factors affecting the post-operative NDI score.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have compared the cervical sagittal parameters [ 2 , 3 , 4 ]. Xu Y [ 2 ] found that an increase in the T1S and NT and a decrease in the CL were risk factors affecting the post-operative NDI score. Kato M [ 3 ] found that after a laminoplasty, patients with C2-7SVA ≥ 35 mm will have a poor quality of life and severe neck pain.…”
Section: Introductionmentioning
confidence: 99%